A Design of a PET Detector Using Micro-Channel Plate Photomultipliers with Transmission-Line Readout - Kim, H. (2010)
A computer simulation study has been conducted to investigate the feasibility of a positron emission tomography (PET) detector design by using micro-channel plate (MCP) photomultiplier tubes (PMT) with transmission-line (TL) read-out and waveform sampling. The detector unit consisted of a 24×24 array of pixelated LSO crystals, each of which was 4×4×25 mm(3) in size, and two 102×102 mm(2) MCP-PMTs coupled to both sides of the scintillator array. The crystal (and TL) pitch was 4.25 mm and reflective medium was inserted between the crystals. The transport of the optical photons inside the scintillator were simulated by using the Geant4 package. The output pulses of the MCP-PMT/TL unit were formed by applying the measured single photo-electron response of the MCP-PMT/TL unit to each individual photon that interacts with the photo-cathode of the MCP-PMT. The waveforms of the pulses at both ends of the TL strips were measured and analyzed to produce energy and timing information for the detected event. An experimental setup was developed by employing a Photonis Planacon MCP-PMT (XP85022) and a prototype TL board for measuring the single photo-electron response of the MCP-PMT/TL. The simulation was validated by comparing the predicted output pulses to measurements obtained with a single MCP-PMT/TL coupled to an LSO crystal exposed to 511 keV gamma rays. The validated simulation was then used to investigate the performance of the proposed new detector design. Our simulation result indicates an energy resolution of ~11% at 511 keV. When using a 400–600 keV energy window, we obtain a coincidence timing resolution of ~323 ps FWHM and a coincidence detection efficiency of ~40% for normally-incident 511keV photons. For the positioning accuracy, it is determined by the pitch of the TLs (and crystals) in the direction normal to the TLs and measured to be ~2.5 mm in the direction parallel to the TLs. The energy and timing obtained at the front- and back-end of the scintillator array also show differences that are correlated with the depth of interaction of the event.